Designing Ubiquitous Information Environments: Socio-Technical Issues and Challenges IFIP TC8 WG 8.2 International Working Conference, August 1-3, 2005, Cleveland, Ohio, U.S.A. - Sørensen, Carsten; Yoo, Youngjin; Lyytinen, Kalle; DeGross, Janice I.; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2005)
The rapid developments in mobile and wireless communication technologies and the continuing miniaturization of computing devices makes ubiquitous information environments more of a technical reality than a distant vision. Ubiquituous computing as the next wave of organizational computing offers new possibilities and opportunities for organizations to improve their productivity and effectiveness. However, the emergence of ubiquitous information environments not only signals opportunities, but also fundamentally challenges many of the traditional assumptions about organizations, management, computing, communication and work. The ubiquitous information environments affect all levels of organization activities. Currently there are a number of activities in designing and implementing ubiquitous information environments. The 7 parts of this book, and the 31 chapters, cover various issues related to the design and implementation of ubiquitous information environments. The book covers old and familiar issues in light of emerging ubiquitous information environments as well as novel social and technical problems. The book brings in diverse perspectives on ubiquitous information environments, from computer-supported collaborative work, institutional perspective, diffusion of innovation, management, sociology, individual cognition, and software engineering. It also covers a variety of technologies that make up ubiquitous information environments including RFID, wireless grid, GPS, mobile phones, and wireless local area network. The papers cover many contexts of ubiquitous computing including personal use, library, automobile, healthcare, police, professional knowledge work, remote diagnostics of machines, and marketing, attesting to the wide range of potential of ubiquitous information environments. This book developed as a collective product of the International Federation for Information Processing (IFIP) Working Group 8.2, a working group dedicated to the study of the interaction of information systems and the organization. The book proceeds from the IFIP Working Conference on the Design of Ubiquitous Information Environments held in Cleveland, Ohio, in August 2005.
Socio-Technical Studies of Mobility and Ubiquity -- Keynotes -- The Future of Work -- Its the Experience, Not the Price -- The Culture of Information: Ubiquitous Computing and Representations of Reality -- Individual Consequences -- Friend or Foe? The Ambivalent Relationship between Mobile Technology and its Users -- The Role of Ubiquitous Computing in Maintaining Work-Life Balance: Perspectives from Women in the Information Technology Workforce -- Reflexivity, the Social Actor, and M-Service Domestication: Linking the Human, Technological, and Contextual -- Privacy Considerations in Location-Based Advertising -- Organizational Impact -- Mobility in the Round: Use of Wireless Laptop PCs in Clinical Ward Rounds -- Beliefs about Computing: Contrary Evidence from a Study of Mobile Computing Use among Criminal Justice Personnel -- Assessing the Mobile-Stationary Divide in Ubiquitous Transport Systems -- The Impact of Ubiquitous Computing Technologies on Business Process Change and Management: The Case of Singapore’s National Library Board -- Ubiquitous Computing and the Double Immutability of Remote Diagnostics Technology: An Exploration into Six Cases of Remote Diagnostics Technology Use -- Wireless Grids: Assessing a New Technology from a User Perspective -- Fluid Organizing of Work in the Ubiquitous Information Environment -- The Reconstruction of Portable Computers: On the Flexibility of Mobile Computing in Mobile Activities -- Development Issues -- Mobile Systems Development: A Literature Review -- Designing Context-Aware Interaction: An Action Research Study -- Approaching Information Infrastructure as an Ecology of Ubiquitous Sociotechnical Relations -- The Slight Surprise of Integration -- Innovation and Diffusion of Ubiquitous Information Environments -- Scaling the Wall: Factors Influencing the Conditions for Market Entry in the Mobile Data Market -- An International Mobile Security Standard Dispute: From the Actor—Network Perspective -- Ordinary Innovation of Mobile Services -- The Ubiquity and Utility of Resistance: Codesign and Personalization of Information Systems -- Position Papers -- CrackBerries: The Social Implications of Ubiquitous Wireless E-Mail Devices -- Building a Ubiquitous Artifact That Integrates Problem-Solving and Learning Processes to Support Creativity -- Effects of Wireless Mobile Technology on Employee Work Behavior and Productivity: An Intel Case Study -- Panels -- Ubiquitous Computing for Health and Medicine -- Socio-Technical Research Challenges in Ubiquitous Computing: The Case of Telematics -- Community-Based Wireless Initiatives: The Cooperation Challenge -- Ubiquitous Computing in Practice.
Keywords: User interfaces (Computer systems).; Computers and civilization; E-commerce.; Education—Data processing; Application software; Computers; User Interfaces and Human Computer Interaction; Computers and Society; e-Commerce/e-business.; Computers and Education; Computer Appl. in Social and Behavioral Sciences; Information Systems and Communication Service